Return migration, space and identity in Daniel Mandishona’s White gods black demons (2009) - Bhowa, Jairos Kudakwashe (Midlands State University, 2017)
This study explores the relationship between return migration, space and identity in Zimbabwean Literature as exemplified by Daniel Mandishona’s White Gods Black Demons (2009). It employs postcolonial theory in its exploration of the relationship between return migration, space and identity in Mandishona’s text. Return migration is largely depicted as a metaphor of failure in most of the selected stories were some of the characters return to their homeland either sickly or mad and ultimately commit suicide. However, the research will also consider the various tactics and strategies that returnees employ to re-integrate in their homelands.